2022
DOI: 10.1101/2022.07.17.22277100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the Influence of the Budget Formulation Structures and Processes on the Efficiency of County Health Systems in Kenya

Abstract: IntroductionPublic Finance Management (PFM) processes guide the translation of government resources to services and determine health system efficiency. PFM processes are implemented within the budget cycle which entails the formulation, execution, and evaluation of government budgets. We examined how the budget formulation structure and processes influence health system efficiency at the county level in Kenya.MethodsWe conducted a mixed methods case study using counties classified as relatively efficient (n=2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…First, weak monitoring and accountability mechanisms potentially reduce the effectiveness of the budget formulation and implementation processes of the budgeting cycle which turn affects the e ciency of county health systems. Our previous work has demonstrated aspects of budget formulation that in uence health system e ciency including, budget ceilings, the budget structure, participatory budget formulation, the pooling and allocation of resources, and budget approval processes (22). We also found that the following aspects of budget execution may in uence health system e ciency -budget credibility, cash disbursement processes, procurement processes, provider autonomy, and nancial management information systems (12).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…First, weak monitoring and accountability mechanisms potentially reduce the effectiveness of the budget formulation and implementation processes of the budgeting cycle which turn affects the e ciency of county health systems. Our previous work has demonstrated aspects of budget formulation that in uence health system e ciency including, budget ceilings, the budget structure, participatory budget formulation, the pooling and allocation of resources, and budget approval processes (22). We also found that the following aspects of budget execution may in uence health system e ciency -budget credibility, cash disbursement processes, procurement processes, provider autonomy, and nancial management information systems (12).…”
Section: Discussionmentioning
confidence: 79%
“…PFM happens within the annual budget cycle which entails the formulation, execution, and monitoring and accountability of the budget (5). Our previous papers discuss how the budget formulation (11) and execution (12) processes in uence health system e ciency in Kenya. This paper focuses on how the budget monitoring and accountability processes in uence county health system e ciency in Kenya.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What we see in Kenya is similar tensions between the county government and subcounty levels that include public health facilities. At the county level, control over resources is concentrated at the county treasury, with other departments, including the county department of health and units under it, such as health facilities having limited power and control over resources 25 26. Given that public health facilities are one of the key sources of locally generated revenues at the county level, county-level actors are reluctant to relinquish control over these resources to public health facilities (figure 1).…”
Section: Determinants Of Public Health Facility Financial Autonomymentioning
confidence: 99%
“…These capacity challenges have manifested in suboptimal budget formulation, execution and monitoring challenges that have affected health facility autonomy (figure 1). 25 26 Capacity challenges as impediments to de facto autonomy have been documented elsewhere 5 6…”
Section: Determinants Of Public Health Facility Financial Autonomymentioning
confidence: 99%